Preparation of Sarah Sjöström and NEC swimmers for the 16th Olymic Games: Common sense, sports science, the art of coaching and altitude training - Vorontsov, A. (Schwimmen: Lernen und Optimieren, 43, 2018)
Author describes the preparation of the Swedish top swimmer Sarah Sjöström and her preparation strategy as coach at the Swedish National Excellence Center in Stockholm in preparation for the Olympic Summer Games 2016. Sjöström won 1x gold and 1x silver in Rio.